UPAYA UPAYA MENINGKATKAN KETERAMPILAN PROSES SAINS (KPS) SISWA KELAS V PADA MATERI SUHU DAN KALOR DI MI COKROAMINOTO 02 TRIBUANA - Dwi, Dwi Purbaningrum (Jurnal Ilmiah Ibtida, 2024)
This research aims to improve students' Science Process Skills (KPS) in class V temperature and heat material at MI Cokroaminoto 02 Tribuana for the 2022/2023 academic year. This type of research uses Classroom Action Research, which is carried out in two cycles. The research subjects were 10 class V students at MI Cokroaminoto 02 Tribuana. This research uses a cycle design developed by Kurt Lewin. The data collection method uses observation sheets and questionnaires. The data analysis techniques used are quantitative and qualitative descriptive. The results of this research show that the science process skills of class V students at MI Cokroaminoto 02 Tribuana have increased. This increase is shown by the average of students' science process skills in the pre-cycle being 42%, in the first cycle it increased to 65% and again in the second cycle to 85%.